Comorbid laboratory abnormalities in female pattern hair loss patients - Hsin-Jou Wang; Jui-Wen Yeh; Yin-Fan Chang; Jin-Shang Wu; Chao-Chun Yang (Wolters Kluwer Medknow Publications, 2022)
Background: Female pattern hair loss (FPHL) is the main cause of alopecia in women and has a debilitating impact on the quality of life. However, certain comorbid conditions causing hair loss are often masked by FPHL and may remain undetected. Hence, it is imperative to identify them to administer appropriate treatment. The necessity of laboratory tests to evaluate these comorbidities in patients with FPHL has not been established. Objectives: This study aimed to identify the frequency of comorbid abnormalities detected by laboratory tests in patients with FPHL. Methods: Routine laboratory test results of patients with FPHL, who visit our hair clinic for the first time, were retrospectively collected and analyzed. These tests assessed the serum testosterone, thyroid-stimulating hormone, free thyroxin, zinc and ferritin levels, hemoglobin, as well as antinuclear antibody (ANA), and rapid plasma reagin test results. The correlation between age and hair loss severity and the frequency of comorbidities was evaluated using subgroup analysis. Results: Among the 356 patients with FPHL, coexisting zinc deficiency, iron depletion, and thyroid abnormalities were common and present in 41.7%, 39.7%, and 11.3% of them, respectively. The rate of concomitantly increased ANA titers was relatively low (4.4%), while that of syphilis and high serum testosterone levels was extremely low (0.3% and 0%, respectively). Younger patients (<50 years) with FPHL had a higher rate of coexisting iron deficiency than patients in the older age group. Conclusion: Testing for concomitant iron depletion, zinc deficiency, and thyroid disease is recommended in female patients with FPHL.